2009
DOI: 10.1007/s11896-009-9050-2
|View full text |Cite
|
Sign up to set email alerts
|

Integration of Pre-Employment Polygraph Screening into the Police Selection Process

Abstract: The authors provide a polygraph primer for police psychologists involved in law enforcement personnel selection. Law-enforcement pre-employment polygraph examinations are a decision-support tool intended to add incremental validity to the personnel selection process. Problems stemming from the use of the polygraph may be related to misunderstanding of the polygraph test and to field practices surrounding the use of polygraphy in the police selection process. Potential problems can result from ineffective selec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 13 publications
1
4
0
2
Order By: Relevance
“…They also opined that the inmate's contention of inherent inaccuracy and imperfection of the polygraph was erroneous and found that the decision had not been made solely on the basis of the polygraph results. This is similar to the standards suggested earlier; polygraphs can be considered as evidence if the results are able to be methodologically triangulated (Handler et al, 2009).…”
Section: Opposition To Polygraphssupporting
confidence: 80%
See 4 more Smart Citations
“…They also opined that the inmate's contention of inherent inaccuracy and imperfection of the polygraph was erroneous and found that the decision had not been made solely on the basis of the polygraph results. This is similar to the standards suggested earlier; polygraphs can be considered as evidence if the results are able to be methodologically triangulated (Handler et al, 2009).…”
Section: Opposition To Polygraphssupporting
confidence: 80%
“…They used a sample of both university students and law enforcement trainees, who were informed of the nature of the experiment. Offe and Offe (2007) (Handler et al, 2009). …”
Section: Support For Polygraphsmentioning
confidence: 99%
See 3 more Smart Citations